Experimental Studies on Dry Sliding Wear Behavior of Air Plasma Sprayed Coatings on 410 Steel. (2017) - Sreenivas Rao, K.V.; Girisha, K.G.; Abhishek, M.; Panindra, T.G.
Abstract: Many industrial applications require surface treatments of engineering materials to improve the service life of the components. Thermal spraying is one of the advanced surface treatments adopted for surface coating. In the present study, Cr2 O3 powder particles of average particle size 50µm were made to deposit on grit blast 410 steel using air plasma spray technique. Ni/Cr was primarily coated on steel substrates as the bond coat to maintain good bonding between coating and substrate. Dry sliding wear studies were carried out using pin-on-disc Tribometer at room temperature for different sliding velocity at constant load and sliding distance as per ASTM G99 standard. Vickers micro hardness and coating porosity were tested and reported. Surface morphologies and chemical composition of developed coatings were observed and analyzed using scanning electron microscope (SEM) and EDX. The experimental results confirm that, Cr2 O3 coating improves the wear resistance and hardness as compared to un-coated substrates.